Prevalence of Malnutrition in Hemodialysis Patients: A Single Center Study. (Pakistan Journal of Kidney Diseases, 2021)
This study was conducted to determine the prevalence of malnutrition inhemodialysis patients. Methodology: This cross sectional study was conducted on all patients of end stage renal disease (ESRD) on maintenance hemodialysis (MHD) at dialysis center of Shaikh Zayed Hospital Lahore (SZH). Patients being dialyzed for more than three months were included in  the study. At start of study demographic data was entered on a pro forma. Laboratory parameters (Hemoglobin, serum albumin, sodium, potassium, calcium, phosphate and uric acid), viral markers (HBsAg & Anti HCV) were measured and BMI was calculated. Results: One hundred and fifty-eight patients were enrolled. Six patients were excluded because they underwent renal transplant. One hundred and fifty-two patients completed study. There were 81(53.3%) males and rest of the patients were females. Mean age of patients was 47.26 ± 15.14 years and half of the patients 76 (50%) were in middle age (40-60 years) group.  Unemployed patients were 99 (65.1%). Ninety-three (62.2%) patients were illiterate or having less than tenth grade of education. Most of the patients 122 (80.3%) were hypoalbuminemic and anemic 126(82.9%). Eighty-seven (57.9%) patients were underweight having BMI less than 20 i.e. malnourished. Ninety-three (61.2%) patients were getting thrice weekly dialysis and rest of them were dialyzed twice weekly. Ninety-four (61.8%) patients were hepatitis C positive.Conclusion: In this study we found that majority of hemodialysis patients were malnourished, hypoalbuminemic and anemic. Continuous nutritional assessment and care must be considered mandatory for dialysis patients to reverse the situation.
Keywords: malmutrition; anemia; chronic kidney disease; hemodialysis; hypoalbuminemia; ESRD